(untitled) (Journal of Pharmaceutical Negative Results, 2023)
HR Analytics has gained immense popularity among the consultants and practitioners in the field of HR management. HR Analytics applies various statistical tools on the collected data to create interventions, propose strategies and assess their effectiveness in the organizational performance of various departments such as marketing, finance, etc. Though the HR Analytics is not less known but has been remained relatively less explored. However, it has not been subjected to scrutiny by academic researchers. The present study, therefore, investigates the impact of HR Analytics on organizational performance and how this relationship is mediated by employee motivation. A descriptive design was adopted and data was collected from HR employees from Bangalore, who adopt analytics for various HR processes. The results showed that motivation partially mediated the effects of HR Analytic on organizational performance. The analytical skills of employees which involves understanding, analyzing and interpreting data has a significant impact on the organizational performance of the organization in terms of improved decision-making and return on investment achieved. Further, motivating employees at work to generate and experiment with new ideas; to customize new ways to deliver products and services by analyzing data; to adopt and use creative analytics in any process; and to find satisfaction at work can further enhance the effectiveness of analytical skills on organizational performance. Based on these results, the study emphasizes the need for developing analytical skills among HR employees and motivating them to increase organizational performance.